Major Challenges for Drone Delivery - A Survey - M.S.Minu , R.Aroul Canessane , (International Journal of Control and Automation, 2020)
In the recent past, technology has come a long way. Unmanned Aerial Vehicles or UAVs, which are colloquially known as drones, are one such advancement primarily driven by industrial efforts for commercialization as it sees a potential market. With the implementation of appropriate regulations, a worldwide deployment is expected. Due to great flexibility in mobility, drones have a wide range of applications, wherein drone delivery service is one such application that proves to be vital for commercialization of drones. Some companies are now employing drones as vehicles for home delivery services. Though the flexibility of drones proves to be greatly useful, there are so many security concerns such as the hijacking of drones for private information, cyber-security, physical safety, Vehicle Routing and Battery Consumption issue etc. This paper focuses on different solutions to mitigate such risks and tackle such issues using methods like cryptography, hashing, routing, EEG,etc. This paper acts as a Literature Survey for the various methods that have been proposed by other scholarly papers to solve these challenges.